2021
DOI: 10.1038/s41598-021-88497-w
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces boulardii modulates oxidative stress and renin angiotensin system attenuating diabetes-induced liver injury in mice

Abstract: Type 1 diabetes (T1DM) is a chronic disease characterized by hyperglycemia due to a deficiency in endogenous insulin production, resulting from pancreatic beta cell death. Persistent hyperglycemia leads to enhanced oxidative stress and liver injury. Several studies have evaluated the anti-diabetic and protective effects of probiotic strains in animal models. In the present study, we investigated, through histopathological and biochemical analyses, the effects of eight weeks of administration of Saccharomyces b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 67 publications
(68 reference statements)
2
5
0
Order By: Relevance
“…It has been reported that hyperglycemia stimulates the generation of ROS and decreases antioxidant defense in the livers of diabetic rats. 38 In our study, the activities of antioxidant factors GSH-PX and SOD were decreased, whereas the level of ROS production was increased in mice with T1DM, which was consistent with previous studies showing that SOD activity was decreased in both STZ-induced diabetic mice and rats. 37 , 38 A previous study has shown that SCL ameliorates lipopolysaccharide-induced acute lung injury by reducing ROS levels.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that hyperglycemia stimulates the generation of ROS and decreases antioxidant defense in the livers of diabetic rats. 38 In our study, the activities of antioxidant factors GSH-PX and SOD were decreased, whereas the level of ROS production was increased in mice with T1DM, which was consistent with previous studies showing that SOD activity was decreased in both STZ-induced diabetic mice and rats. 37 , 38 A previous study has shown that SCL ameliorates lipopolysaccharide-induced acute lung injury by reducing ROS levels.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, fungi from the Saccharomyces family are known to have beneficial effects on patients with DM, by improving blood-sugar levels, dyslipidemia, alveolar bone destruction, hepatic inflammation (as shown by a reduction in the transaminase serum levels) and by modulation of the immune response (as shown by the reduction of serum TNF-α levels) ( 52-54 ). A previous study performed on C57BL/6 mice with streptozotocin-induced diabetes demonstrated that administrating Saccharomyces boulardii through intraperitoneal injections during an 8-week period reduced hepatic hydropic degeneration and hepatic vascular congestion, diminished oxidative stress (by reducing carbonylated proteins, and increasing the activity of the antioxidant enzymes superoxide dismutase and glutathione peroxidase) and normalized concentrations of the renin-angiotensin-aldosterone system peptides (affecting both the liver and the kidneys) ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“… 88 There are many types of probiotics, such as Bifidobacterium bifidus, Lactobacillus , and Saccharomyces boulardii , of which S. boulardii is probably the most commonly used probiotic fungi. Animal studies have confirmed that S. boulardii could change gut microbiota and attenuate liver injury, inflammation, 89–91 and fibrosis, 92 potentially indicating its protective and therapeutic role in liver diseases. A recent study revealed that most strains of Saccharomyces and non-Saccharomyces yeasts evaluated in their work are safe microorganisms, and those could be regarded as a valid alternative to the widely available probiotic yeast S. boulardii .…”
Section: Gut Mycobiomementioning
confidence: 95%